What the Mean Measures of Mobility Miss: Learning About Intergenerational Mobility from Conditional Variance - Md. Nazmul Ahsan; M. Shahe Emran; Hanchen Jiang; Forhad Shilpi (Global Labor Organization (GLO), 2022)
A large literature on intergenerational mobility focuses on the conditional mean of children's economic outcomes to understand the role of family background, but ignores the information contained in conditional variance. Using exceptionally rich data free of coresidency bias, we provide evidence on three large developing countries (China, India, and Indonesia) that suggests a strong influence of father's education on conditional variance of children's schooling. We find substantial heterogeneity across countries, gender, and geography (rural/ urban). Cohort based estimates suggest that the effects of father's education on the conditional variance has changed qualitatively, in some cases a positive effect in the 1950s cohort turning into a substantial negative effect in the 1980s cohort. We develop a methodology to incorporate the effects of family background on the conditional variance along with the standard conditional mean effects. We derive risk adjusted measures of relative and absolute mobility by accounting for an estimate of the risk premium for the conditional variance faced by a child. The estimates of risk adjusted relative and absolute mobility for China, India and Indonesia suggest that the standard measures substantially underestimate the effects of family background on children's educational opportunities, and may give a false impression of high educational mobility. The downward bias is specially large for the children born into the most disadvantaged households where fathers have no schooling, while the bias is negligible for the children of college educated fathers. The standard (but partial) measures may lead to incorrect ranking of regions and groups in terms of relative mobility. Compared to the risk adjusted measures, the standard measures are likely to underestimate gender gap and rural-urban gap in educational opportunities.
Keywords: I24; J62; O12; 330; Conditional Variance; Family Background; Intergenerational Educational Mobility; Risk Adjusted Mobility Measures; China; India; Indonesia